Validity of the wingate anaerobic test for the evaluation of elite runners - Legaz Arrese, A.; Munguia-Izquierdo, D.; Carranza-Garcia, L. E.; Torres-Dávila, C. G. (The Journal of Strength and Conditioning Research, 2011)
This study aimed to determine performance differences, based on the Wingate anaerobic test (WAnT), between homogeneous groups of elite male and female runners competing at distances ranging from 100 m to the marathon. We also attempted to establish a link between running ability and performance as measured by the WAnT. In total, 116 world-class runners (86 men and 30 woman) volunteered to participate in our study. Subjects were tested for peak power (PP, 5-second output) and mean power (MP, 30-second output) using WAnT procedures. Runners were classified into groups according to their best performances times. For male runners, PP and MP outputs decreased with increasing distance (p < 0.001). This trend was also true for female runners (p < 0.005). However, for both sexes, there were no significant differences in the PP values among 100-, 400-, and 800-m runners, and there were also no differences in the MP values for subjects that ran distances of 100 m compared with the values for subjects that ran distances of 400 and 800 m. In addition, no significant differences were observed in the PP and MP values between subjects that ran distances of 800, 1,500, and 3,000 m. Performance in the WAnT was not significantly associated with running performance in any distance event. The results of this study indicate that the WAnT is not a useful tool for the evaluation of elite runners.